How to scrap fuel subsidies - Kyle, Jordan; Andam, Kwaw S. (Project Syndicate, 2023)
Many oil-producing countries have long maintained domestic fuel subsidies, even as the fiscal cost has ballooned, for fear of triggering civil unrest. But Nigerian President Bola Tinubu’s decision to take a “cold turkey” approach to ending his country’s subsidies, and the lack of popular resistance to the move, suggests a way forward.